Relationship Between Family Support And Active Participation Of The Elderly Attending Elderly Health Posts In Tanjung Raja Village Deli Serdang District, 2025 - Nisa El Hasanah; Andhika Budi Sentoso; Lilla Sarissa Br Ginting (Medistra Medical Journal (MMJ), 2025)
The elderly are a group that is vulnerable to health problems, thus requiring extra attention to maintain their quality of life. One measure taken is to increase active participation in the Elderly Posyandu programs. This study aims to identify the relationship between family support and the level of participation og the elderly in Posyandu activities in Tanjung Raja Village, Deli Serdang Regency, in 2025. The study applied a quantitative approach with a cross-sectional design. The research subjects were 42 elderly  individuals selected using a total sampling technique. Data collection was conducted using questionnaires and attendance lists, and then analyzed using the Chi-square test. The study findings revealed that most respondents received family support (59,5%), but the majority of elderly were classified as less actively involved in Posyandu activities (69,0%). Statistical analysis resulted in a p-value of 0.060. Statistical analysis yielded a p-value of 0.060, indicating no significant relationship between family assistance and elderly participation. It is recommended that families continue to provide full support, while posyandu cadres reinforce education to families about the importance of elderly involvement in posyandu programs.